Sangkrek Gemilang: Membangun Masyarakat Unggul Serta Mengangkat Potensi Lokal Untuk Mewujudkan Masa Depan Yang Cemerlang Di Dusun Sangkrek - Wanna, Adillah Alfaizu; Muzakki, Mochammad Iqbal; Cahyaningrum, Dyah Oktaviana; Rustan, Ikbar Kausar; Sarjono, Stevany Lousiana; Maheswara, Dyuta Aryasatya; Sherly, Putri Mina; Prayoga, Rihandias Tegar; Anfasa, Anfasa; Praditaningrum, Praditaningrum; Trimaharanti, Divia; Suprabowo, Imam (Universitas Muhammadiyah Yogyakarta, 2024)
Community Service Program (KKN) is a form of learning for students that allows them to be directly involved in community life. At Universitas Muhammadiyah Yogyakarta, students carry out KKN in Sangkrek Hamlet with the aim of providing empowerment, training, counseling, mentoring, and assistance to the local community. Through KKN, students act as agents of change who are actively involved in community dynamics, with a focus on improving the quality of life and development. The observation methods used include question and answer, documentation, and direct observation to the field. The results of these observations help determine the work program of KKN group 091, which is divided into physical and non-physical programs. The physical programs include recycling collection, village community service, making a map of residents' parcels, making the Karang Taruna structure wall, and agricultural activities with the Women Farmers Group. Meanwhile, non-physical programs involve PAUD assistance, tutoring, Posyandu assistance, and healthy gymnastics activities. Students in KKN act as facilitators, dynamics, and motivators in the implementation of these programs. The implementation of KKN was carried out from January 11, 2024 to February 11, 2024 and ran smoothly and received assistance from the community. Residents of Sangkrek Hamlet support and actively participate in the implementation of the KKN work program, so that the implemented program can be directly benefited by both students and residents of Sangkrek Hamlet. It is hoped that after KKN ends, the people of Sangkrek Hamlet can continue to develop the potential of themselves and their environment, and maintain the activities that have been carried out as capital for the future.